Regulating green bonds in the People's Republic of China: Definitional divergence and implications for policy making - Hao Zhang (Asian Development Bank Institute (ADBI), 2020)
The first green bond was issued in the People's Republic of China (PRC) in 2015 and since then the PRC has become a significant player in the world's green bond market. In just three years, green bond issuance in the PRC has skyrocketed from almost none to the country becoming one of the largest issuers globally. Given the nascency of the green bond market in the PRC, there are still two main questions that remain under-researched in the relevant scholarship. The first question relates to whether the multiple definitions of green bonds and the eligible use of proceeds under the Chinese regulations are consistent with international standards. The second question centers on the degree of divergence of the transparency requirements under the Chinese regulations themselves. Using doctrinal and comparative analysis, this article investigates these two questions by examining the relevant Chinese regulations and international standards that underpin the green bond issuance. This article discovers that, despite the fact that the various definitions in relation to green bonds that are provided by the multiple Chinese regulations are generally consistent, there are still some slight differences between them in terms of the eligible uses of green proceeds. These differences may potentially affect lenders' assessment of investments and impact their decisions as to whether to provide financing to the issuer.
Keywords: K29; 330; green bonds in the People's Republic of China; eligible use of proceeds; information disclosure; Chinese regulations